Diversification of Gene Expression during Formation of Static Submerged Biofilms by Escherichia coli - Besharova, Olga; Suchanek, Verena M.; Hartmann, Raimo; Drescher, Knut; Sourjik, Victor (Frontiers in Microbiology, 2016)
Many bacteria primarily exist in nature as structured multicellular communities, so called biofilms. Biofilm formation is a highly regulated process that includes the transition from the motile planktonic to sessile biofilm lifestyle. Cellular differentiation within a biofilm is a commonly accepted concept but it remains largely unclear when, where and how exactly such differentiation arises. Here we used fluorescent transcriptional reporters to quantitatively analyze spatio-temporal expression patterns of several groups of genes during the formation of submerged Escherichia coli biofilms in an open static system. We first confirm that formation of such submerged biofilms as well as pellicles at the liquid-air interface requires the major matrix component, curli, and flagella-mediated motility. We further demonstrate that in this system, diversification of gene expression leads to emergence of at least three distinct subpopulations of E. coli, which differ in their levels of curli and flagella expression, and in the activity of the stationary phase sigma factor σS. Our study reveals mutually exclusive expression of curli fibers and flagella at the single cell level, with high curli levels being confined to dense cell aggregates/microcolonies and flagella expression showing an opposite expression pattern. Interestingly, despite the known σS-dependence of curli induction, there was only a partial correlation between the σS activity and curli expression, with subpopulations of cells having high σS activity but low curli expression and vice versa. Finally, consistent with different physiology of the observed subpopulations, we show striking differences between the growth rates of cells within and outside of aggregates.